2017
DOI: 10.5812/ijcm.11599
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Microsatellite Instability in Ovarian Epithelial Cancers Detected by Molecular Genetic Studies in a Sample of Iranian Women

Abstract: Background: Microsatellite instability, the main genetic element in HNPCC syndrome, is associated with a number of cancers, including ovarian epithelial carcinomas. These cancers have distinct characteristics compared to non-MSI related ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The macroscopic features of the OC subtypes in our cohort were typical of malignant OCs. [28,35] Most of our cases were unilateral with stage I disease, without capsular breach or LVI, which is concordant with a study by Shahsiah et al [19] Early-stage (FIGO stage I/II) ovarian tumours may involve one or both ovaries or fallopian tubes with extension below the pelvic brim or primary peritoneal cancer. [5] These early-stage OCs have a 5-year survival rate of 92%, which emphasises the importance of implementing screening and effective treatment options in early-stage disease to prevent development to advanced stages where patient survival decreases significantly.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The macroscopic features of the OC subtypes in our cohort were typical of malignant OCs. [28,35] Most of our cases were unilateral with stage I disease, without capsular breach or LVI, which is concordant with a study by Shahsiah et al [19] Early-stage (FIGO stage I/II) ovarian tumours may involve one or both ovaries or fallopian tubes with extension below the pelvic brim or primary peritoneal cancer. [5] These early-stage OCs have a 5-year survival rate of 92%, which emphasises the importance of implementing screening and effective treatment options in early-stage disease to prevent development to advanced stages where patient survival decreases significantly.…”
Section: Discussionsupporting
confidence: 91%
“…[10] Our cohort comprised 19 cases owing to exclusion of serous OCs. Although serous subtypes account for ~75% of all EOCs, they are not associated with MMR-d. [3,8,19] The overall patient ages and ovarian tumour subtypes in our study correspond to those in global studies. [6,19,[28][29][30][31][32] Infrequent capsular breach (21.1%) and LVI (15.8%) were observed in our cohort, whereas a study on EOC in Japanese women showed ovarian capsular breach and LVI in 55.8% and 17.5% of cases, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The related primers were ordered from Macrogene Company (Geum Chun-Gu, Seoul, Korea). These primers were tagged by Hex or Fam fluorescent dyes at 5* sequences (8). The real-time PCR was performed for the target genes in 20 μL reaction volume including 10 μL of 2X SYBR Green master mix without Rox (Ampliqon, Stenhuggervej, Denmark), 50 ng of the extracted DNA, and 1 μL of both reverse and forward primers which were prepared at 10 pM/μL concentration.…”
Section: Msi Analysis By Dna Sequencingmentioning
confidence: 99%
“…The first report of MSI contributing to human cancer was published in 1993, describing 28% of MSI in colon tumors examined (61). Since then, the role of MSI has been discovered in many different types of cancer (9,11,32,56,65). However, instability in mitochondrial DNA (mtDNA) is still insufficiently characterized and is not well studied.…”
Section: Siti Muslihah Abd Radzakmentioning
confidence: 99%